Response of Freesia Hybrida Plant to Spraying with Roselle Calyx Extract (Hibiscus Sabbdariffa L.) and Vitamin B1 Extract in Growth Characteristics - Arshad Naji Alhasnawi (Journal of Global Pharma Technology, 2018)
An experiment was conducted at the nursery of Agriculture Faculty during growing season 2014 – 2015 to study the effect of spraying Roselle extract and vitamin B1 on growth and flowering characteristics of freesia plant. Experiment was adopted a Randomized Complete Block Design (R.C.B.D) with three replicates in two factors, First three concentration of spraying Roselle calyx extract i.e. (0, 5 and 10) g.L-1. Second three concentration of vitamin B1 i.e. (0, 20 and 40) mg. L-1. Means were compared by using Least Significant Difference (L.S.D) test at a probability of 0.05.   Results showed that spraying Roselle calyx extract at a concentration 10g.L-1 and vitamin B1 at concentration 20mg. L-1 increased the number of leaves per plant significantly to 8.67, shoot dry weight to 4.66g, content of chlorophyll A,B and Total in leaves to 56.01,25.00 and 68.09mg. 100g-1 fresh weight, inflorescence stalk length to 26.67cm, diameter of floret to 4.67cm, number of floret to 11.67floret, inflorescence -1, and number of corm to 3.67corm. plant-1, diameters of corm to1.63cm and decreased number of day to flowering time to 125.00 day, compared to the control which gave the lowest values( 3.87life. plant-1, 1.26g, 42,44, 12.51 and 53.0409mg. 100g-1 fresh weight, 14.40cm, 2.67mm,4.67 floret. inflorescence -1, 2.00corm. plant-1 and 1.03cm) and increased number of days  to flowering time to 140 days.                                                                                                                                  Keywords: Freesia Hybrida, Vitamin B1 (Thiamin), Roselle Plant (Hibiscus Sabbdariffa L.) Extract.